Movements and social behavior of killer whales (Orcinus orca) off the Brazilian coast - Athayde, Aline; Cantor, Mauricio; Cardoso, Júlio; Francisco, Arlaine; Santos, Frank Pereira dos; Crespo, Heitor; de Morais, Marcel Vinicius; Albaladejo, Manuel da Cruz; Gallo Neto, Hugo; Siciliano, Salvatore (Frontiers in Marine Science, 2023)
Killer whales (Orcinus orca) are cosmopolitan apex predators that occupy important ecological roles and show some variations in feeding and social habits in coastal and pelagic environments worldwide. Although they have been regularly reported along the Brazilian coastline, their natural history in these tropical and subtropical waters remains poorly understood. Here, we provide new information on group size, behavior, movements and the first assessment of their social structure in Brazilian coast. From 2005 to 2021, 57 new records of sightings were opportunistically observed with estimated group sizes ranging from 1 to 11 individuals (mean = 5.61; SD = 2.91), and 47 individuals were photo-identified—28% adult females, 19% adult males, 19% juveniles, 17% calves and 17% adults of unknown sex. Thirty-one individuals (66%) were sighted just once and sixteen (34%) were resighted more than once (resighting rate = 0.30 ± 0.30 SD). Killer whales were observed feeding on rays four times (two out of which on butterfly rays Gymnura altavela), twice on an unidentified fish school of fish, while attacks on marine mammals were recorded. Between 2020 and 2021, photo-identification results of 11 specific individuals revealed both long and short-distance movements from the southeastern and southern Brazilian coasts to the coast of Uruguay. Individuals seem to be resighted together over time, as suggested by the average half-weight association index (HWI = 0.29 ± 0.19 SD) and a permutation test rejecting the null hypothesis of random association (CVreal = 0.67 > CVmean = 0.01, pCV = 1.00), forming small groups of mixed age-sex that engage in both short- and long-term associations. These patterns suggest that they could form stable social units that also experience some degree of fission-fusion dynamics. While the nature of the opportunistic data hinders a definitive portrayal of the social structure of killer whales using the Brazilian coastal waters, these novel insights contribute to mapping the socio-ecology and behavioral diversity of one of the most widely distributed mammals.